Acceptability of a Microbiome-Directed Food for the Management of Children with Uncomplicated Acute Malnutrition in Maradi, Niger: Two Randomized Crossover Trials - Susan M Rattigan; Ibrahim Ngoumboute Mbouombouo; Mohamed Antar Abdou Tahirou; Ishita Mostafa; Kazi Nazmus Saqeeb; Souna Garba; Ousmane Guindo; Tahmeed Ahmed; Michael J Barratt; Jeffrey I Gordon; Christopher R Sudfeld; Rebecca F Grais; et al. (Current Developments in Nutrition)
Background: A novel ready-to-use microbiome-directed food (MDF) has been developed for the management of acute malnutrition using ingredients that promote repair of the gut microbiota of undernourished children. Objectives: This study aims to assess the acceptability of MDF compared with standard nutritional care among children with acute malnutrition. Methods: Two randomized crossover trials consisting of 2 14-d periods of at-home consumption were conducted. Children aged 6 to <24 mo with severe acute malnutrition (SAM) or moderate acute malnutrition (MAM) were individually randomized in a 1:1 ratio to the sequence of receiving MDF then standard nutritional care, or vice versa. Standard nutritional care consisted of ready-to-use therapeutic food for SAM and ready-to-use supplementary food for MAM. The primary outcome was at-home acceptability, defined as the return of ≥75% of sachets empty after the 14-d at-home consumption period. The primary analysis was a noninferiority analysis, in which MDF was considered noninferior if the lower bound of the 95% confidence interval (CI) of the difference in at-home acceptability comparing MDF with standard nutritional care was within −20 percentage points. Secondary outcomes included caregiver’s perception of the child’s liking, as well as caregiver willingness to use in the future and preference between the 2 foods. Results: In all, 128 children with SAM and 146 children with MAM were randomized. MDF was noninferior to standard nutritional care in terms of at-home acceptability among children with SAM (risk difference: −7.0; 95% CI lower bound: −11.6%) and among children with MAM (risk difference: −2.3%; 95% CI lower bound: −6.1%). There were no differences in caregiver willingness to use either food in future. Conclusions: MDF is acceptable for the management of acute malnutrition in children aged 6 to <24 mo in Niger and should be further tested in other populations with a high prevalence of acute malnutrition. Effectiveness of the novel food will be assessed in forthcoming trials. Trial registration number: This trial was registered at clinicaltrials.gov as NCT05551819.